I sogni di metamorfosi nel mondo antico - Alessandro Baccarin (Lexicon Philosophicum)
The widespread metamorphic imagery of the ancients responded to a pattern of civilisation: metamorphosis was something that everyone could experience in the world and which, precisely because it was linked to something real, could be the subject of dreamlike fantasy. As an ‘everyday’ experience, metamorphosis also acquired its own everydayness in the dreamlike imagination. Our short note examines three dream narratives: the dream of Astiage in Erodotus, the metamorphic dreams of Artemidorus Daldianus, and finally the fourth dream of the Martyr Perpetua in her hagiography. In these dream narratives we find symbolism common to the oneiromantic tradition of the Ancient Near East and Pharaonic Egypt.